Methionine Metabolism Shapes T Helper Cell Responses through Regulation of Epigenetic Reprogramming - Roy, Dominic G.; Chen, Jocelyn; Mamane, Victoria; Ma, Eric H.; Muhire, Brejnev M.; Sheldon, Ryan D.; Shorstova, Tatiana; Koning, Rutger; Johnson, Radia M.; Esaulova, Ekaterina; Williams, Kelsey S.; Hayes, Sebastian; et al. (Cell metabolism, 2020)
Epigenetic modifications on DNA and histones regulate gene expression by modulating chromatin accessibility to transcription machinery. Here we identify methionine as a key nutrient affecting epigenetic reprogramming in CD4+ T helper (Th) cells. Using metabolomics, we showed that methionine is rapidly taken up by activated T cells and serves as the major substrate for biosynthesis of the universal methyl donor S-adenosyl-L-methionine (SAM). Methionine was required to maintain intracellular SAM pools in T cells. Methionine restriction reduced histone H3K4 methylation (H3K4me3) at the promoter regions of key genes involved in Th17 cell proliferation and cytokine production. Applied to the mouse model of multiple sclerosis (experimental autoimmune encephalomyelitis), dietary methionine restriction reduced the expansion of pathogenic Th17 cells in vivo, leading to reduced T cell-mediated neuroinflammation and disease onset. Our data identify methionine as a key nutritional factor shaping Th cell proliferation and function in part through regulation of histone methylation. [Display omitted] •Activated T cells use exogenous methionine to synthesize the methyl donor SAM•Methionine restriction reduces intracellular SAM and H3K4me3 levels in T cells•Methionine restriction limits the expansion of inflammatory Th17 cells•EAE onset and severity are reduced by dietary methionine restriction CD4+ T helper (Th) cells are central drivers of autoimmune pathology in diseases such as multiple sclerosis. Roy and Chen et al. identify methionine as an essential nutrient for Th cell epigenetic programming and demonstrate that dietary methionine restriction impacts T cell-mediated autoimmunity through effects on Th17 cell proliferation and cytokine production.